PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 171 PEKANBARU - ', Lisnarita; ', Erlisnawati; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the student achievement of social studies fifth graderes SDN 171 Pekanbaru still low with an average value of 55,25 and minimum completenness criteria (KKM) social studies is 75. Between students, amounting to 36 people only 15 students who achieve classical KKM with 42%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of Quantum Teaching can improve students achievment of social studies at SDN 171 Pekanbaru. The research was conducted on march 9, 2014 to april 25, 2015 by 2 cyclees. Subjects were students of SDN 171 Pekanbaru, totalling 36 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models Quantum Teaching type of activity the teacher in the lerning process in cycle I frist meeting was 62,5% and at the second meeting of teacher activity increased by 8,3% to 70,8%. cycle II firs meeting and the second meeting of activity increased by 8,4% to 79,2% and the second meeting of activity increased by 12,5% to 95,8%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 54,2% and at second meeting of activity increased 8,3% to 62,5%% and a second meeting of activity increased 16,7% improve to 79,2%. At the firs meeting of the second meeting of activity increased 12,5% to 91,7%%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 56,3%. In the first cycle improve an average of 66,7% with increase as 75,0% and an impove in the second with an average of 83,3% with increase as 9,5%. Result in the research that the implementation of cooperative learning model of Quantum Teaching) can improve students achievement of social Studies at fifth graderes SDN 171 Pekanbaru.Key Words : Model Learning Quantum Teaching, Fave graderes students Achievement.2